A new depsidone derivative from mangrove sediment derived fungus Lasiodiplodia theobromae. Issue 15 (3rd August 2019) - Umeokoli, Blessing O.; Ebrahim, Weaam; El-Neketi, Mona; Müller, Werner E. G.; Kalscheuer, Rainer; Lin, Wenhan; Liu, Zhen; Proksch, Peter
Abstract: A new depsidone derivative botryorhodine I (1 ), along with eight known compounds (2-9 ) were obtained from solid rice cultures of the fungal strain, Lasiodiplodia theobromae M4.2-2 isolated from a mangrove sediment sample. The structures of the isolated compounds were elucidated on the basis of 1 D and 2 D NMR analysis as well as by HRESIMS. All compounds were evaluated for their cytotoxic potential against the mouse lymphoma cell line L5178Y as well as for their antibacterial activities against a panel of Gram-positive and Gram-negative bacterial strains. Compound3 revealed potent cytotoxic activity with an IC50 of 7.3 µ M whereas compound7 showed selective anti-bacterial activity against different S. aureus and E. faecium bacterial strains with MIC value of 25 µg/ml. Graphical Abstract: